Mycobacterium bovis Bacillus Calmette-Guérin Cross-Contamination in the Operating Room: A Case Report. (December 2021) - Aqua, Jasmine Ko; Holdsworth, Jill; Burd, Eileen; Jacob, Jesse T.; Ray, Susan M.; Schechter, Marcos C.
Mycobacterium tuberculosis complex (MTBC) false-positive cultures are commonly attributed to laboratory cross-contamination, but cross-contamination in the operating room (OR) is seldom reported. We report an investigation of cross-contamination in the OR for our case patient, who underwent surgical intervention for a chronic, left-sided breast lesion. Although the case patient had never received Mycobacterium bovis bacillus Calmette-Guérin (BCG) vaccine or chemotherapy, a subsequent surgical sample culture was identified as MTBC by high-performance liquid chromatography and M. bovis BCG-type by genotyping. A collaborative false-positive investigation was initiated, and we discovered a cross-contamination event in the OR from a source case who received BCG intravesical instillation. Clinicians, public health, and infection control staff should be aware that MTBC cross-contamination in the OR is rare, but possible, and should recognize the importance of conducting thorough false-positive investigations.